Investigation for the effect of redeposited Mg particles on the discharge characteristics in an alternating-current plasma display panel. (4th March 2017) - Park, Choon-Sang; Parsons, Travis; Kim, Dong Ha; Kim, Hyun-Jin; Seo, Heaseok; Kim, Sung-O; Shin, Bhum Jae; Tae, Heung-Sik
ABSTRACT: In this paper, the influences of the redeposited Mg particles in the boundary image sticking region on the electron emission of the MgO surface and related discharge characteristics of an alternating-current plasma display panel were examined by using the cathodoluminescence and intensified charge-coupled device techniques. The experimental results showed that the electron emission at the redeposited region of the Mg particles on the MgO surface was intensified and concentrated compared with those for nonredeposited region of the Mg particles, thereby resulting in extremely improving the discharge characteristics in the 42 in high definition (HD) alternating-current plasma display panels (ac-PDPs) with a He (35%)-Xe (11%)-Ne contents.